STROMGREN PHOTOMETRY AND SEARCH FOR SHORT PERIOD VARIABLES IN THE OPEN CLUSTERS NGC 6910 AND NGC 6913 - Pena, J. H.; Peniche, R.; Garcia Cole, A.; Plascencia, J. C.; Parrao, L.; Pena, R. (Одеські астрономічні публікації, 2017)
Analysis of the absolute uvby photometry of the Open Clusters NGC 6910 and NGC 6913 show well-defined peaks that clearly define the accumulation of stars. Differential photometry of five stars in the direction of each cluster determines that at least two stars in each cluster are variables. For NGC 6910 both belong to the cluster and are δ Scuti stars and for NGC 6913 two short period variables one does not belong to the cluster and it might be a δ Scuti star. The other one is a B type star and it belongs to the cluster.